Hired daughters : domestic workers among ordinary Moroccans - Montgomery, Mary, 1986- (Indiana University Press, 2019)
Mary Montgomery examines why Moroccans so often talk about their domestic workers as daughters, what this means for workers and employers, and how this is changing in contemporary Morocco.